Lovkost' i koordinacija v sisteme fizicheskoj podgotovki zanimajushhihsja, specializirujushhihsja v sportivnoj bor'be i boevyh iskusstvah - Nikitenko, A. (Science in Olympic Sport, 2017)
The article is an analytical review on the development of agility in athletes specializing in athletic wrestling and martial arts. The current training methodology in these sports is scrutinized, which is based on the technical and tactical preparation and advancement combined with clearly insufficient attention to the physical training, especially focused on the development of agility as a quality essential for fast and efficient motor actions in changing and unexpected conditions. The differences between sports wrestling and martial arts are identified, which determine the differentiation methodologies for agility development. It is shown the importance for agility development of knowledge of the physiological principles of motor control and such concepts as "motor memory", "motor field", "anticipation", "unconscious automated movements and actions", and "automatisms".